National Athletic Trainers' Association position statement: Preventing sudden death in sports - Casa, D. J.; Guskiewicz, K. M.; Anderson, S. A.; Courson, R. W.; Heck, J. F.; Jimenez, C. C.; McDermott, B. P.; Miller, M. G.; Stearns, R. L.; Swartz, E. E.; Walsh, K. M. (Journal of Athletic Training, 2012)
Objective: To present recommendations for the prevention and screening, recognition, and treatment of the most common conditions resulting in sudden death in organized sports. Background: Cardiac conditions, head injuries, neck injuries, exertional heat stroke, exertional sickling, asthma, and other factors (eg, lightning, diabetes) are the most common causes of death in athletes. Recommendations: These guidelines are intended to provide relevant information on preventing sudden death in sports and to give specific recommendations for certified athletic trainers and others participating in athletic health care.